Guidelines for Enrolling in Florida's BMP Program for Vegetable Crops - Aparna Gazula; Eric Simonne; Brian Boman (EDIS)
HS-1114, a 17-page illustrated fact sheet by Aparna Gazula, Eric Simonne, and Brian Boman, describes this voluntary program for vegetable producers, how to sign up, human and online resources for participants, how to select appropriate best management practices, and the free mobile irrigation labs that are available for making customized recommendations. Published by the UF Department of Horticultural Sciences, August 2007.